STRATEGIES OF RELIGIOUS MODERATION HOUSE IN RUNNING ITS ROLE ON PTKI - Ilmudinulloh R; Gunawan E; Bustomi A; Isroani F (Vol. 2 No. 1 (2024): Proceeding of International Conference on Cultures & Language 2024, 2022)
The mainstreaming of religious moderation is included in the 2020-2024 National Medium Term Development Plan (RPJMN) compiled by Bappenas. PTKI (Islamic Religious Colleges) has a strategic role in strengthening religious moderation by establishing RMB (Religious Moderation House) as the Leading Sector in the internalization of moderate religious understanding in the campus environment. However, the position of RMB in terms of the organization in several Islamic colleges is still unclear, thus affecting the sources of institutional funding. The purpose of this study is to describe RMB's strategies in running its role as leading sector on PTKI. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The data were then analyzed using the Huberman technique which consisted of data collection, data presentation, data reduction, and conclusions. The credibility of the data was tested using a triangulation technique of methods and data sources. The results showed that the RMB strategies to play its role consisted of 1) focusing on virtual world activities that minimized the use of budgets such as building social media networks by creating official institutional accounts on the website, Instagram, Facebook, YouTube, etc., 2) developing creative and interactive contents with messages and activities of religious moderation, 3) facilitating lecturers and students who wish to disseminate the results of their thoughts and research related to religious moderation, and 4) compiling a book containing a collection of articles from the RMB management as a final project.